(untitled) (Journal of Philosophy Culture and Political Science, 2015)
This article discusses the role of religion in Kazakhstan, as well as religious formations in the present territory of the Kazakh people. Since religion is a factor that can directly or indirectly affect society as a whole and the socio-economic development of the state. Given the need for a comprehensive, objective systematization of religious situation in the emphasis on the need to give due attention to and support for religious issues at the state level. The author classifying historical facts, analyzes the religious changes and transformations that have emerged as a result of the influence of the modern processes of religion. Key words: Kazakhstan, state, religion, society, religious modernization.